Study of the Overseas Educational Missions in the Self-Strengthening Movement - Ge, Yi (Kansas State University. Dept. of History, 2012)
The two overseas educational missions launched in the late Qing dynasty were China’s first two officially supported educational missions to the United States and Europe. The two overseas missions were part of the Self-Strengthening Movement’s efforts to modernize China with Western technology and science. Despite the vast research by historians on the first educational mission to the United States and the Self-Strengthening Movement, little is known about the second educational mission to Europe. This study focuses on the two missions and explores the defects of the Self-Strengthening Movement’s impact upon the two missions. The lack of nation-wide commitment and the conservative motivations within the government were the two greatest defects of the Self-Strengthening Movement. The defects of the Self-Strengthening Movement hindered the development of both overseas educational missions and made it impossible to give full scope to the role of the two missions.
Keywords: Self-Strengthening movement; overseas study; Yung Wing; Shen Baozhen; Li Hongzhang; Fuzhou Shipyard